Critical Race Theory and Empirical Sociology. (July 2021) - Christian, Michelle; Seamster, Louise; Ray, Victor
We argue that empirical sociology would benefit from a greater engagement with critical race theory (CRT). In this introduction, we outline four steps to the empirical application of CRT in sociology: (1) understanding that social science is not value neutral, (2) using CRT to inform research design and methodology, (3) investigating racism at multiple levels of analysis, and (4) empirical data and analysis should uncover the relational aspect to racism. The studies in this special issue demonstrate how CRT and social science cross empirical boundaries in fruitful collaboration to document the reproduction of racism in the 21st century.